The Product of Formal Innovation in Contemporary Interior Design Techniques - Muhammad JarAllah Tawfiq; Rouwaida Ra'ed Muhammad (Journal of Techniques)
The product of formal innovation has become a strategy in itself, and because the design development with a technical dimension has become a feature of human life, so the concerned institutions have been referring to this through architecture, including the interior spaces it contains, especially at the level of all materials and raw materials.Therefore, in recent years a phenomenon has emerged that is characterized by the innovation of new design techniques, as the interior designer began to realize the importance of innovation, renewal and development through aesthetic and creative data that takes into account the formation of a future vision in which factors concerned with technical development in contemporary interior design overlap, and by informing researchers about foreign design techniques .Therefore, the problem of the research study was formulated with the following question: Does the product of formal innovation have a role in contemporary interior design techniques? While the importance of research contributes to supplying libraries, especially in the field of interior design, with valuable information that can be referenced by specialists in the field of interior design.While the current research aims to reveal contemporary interior design techniques to reach an innovative design product that achieves the functional and aesthetic aspect of the interior space, while the third chapter includes defining the topic of the research procedures represented by the research methodology based on the descriptive analytical approach, while the research community focuses on adopting the eclectic method Finally, the fourth chapter included extracting the results and conclusions of the research study in addition to the recommendations and suggestions.